The Effectiveness of Resolving Donation-Based Crowdfunding Disputes on the Kitabisa.com Platform Through Alternative Dispute Resolution - Herdifa Pratama; Johari (Mabadi Iqtishad Al Islami, 2024)
In the modern era, financial services have increasingly integrated with technological advancements, one example being donation-based crowdfunding that operates through online financial platforms. Kitabisa.com is an online platform that facilitates donation transactions between campaigners and donors but does not assume responsibility for the actions or information provided by campaigners, donors, or other users. This creates significant potential for disputes among these parties. This study examines two key issues related to the standard contracts used in donation-based crowdfunding: the unilateral dispute resolution provisions created by the platform and the effectiveness of resolving disputes through alternative dispute resolution (ADR). Using a case study approach focused on Kitabisa.com's standard contracts, the research employs descriptive-qualitative analysis of collected data and literature. The findings reveal that while some contracts include ADR clauses, others do not, and the effectiveness of ADR in resolving disputes is limited, with few cases being publicly reported.